Designing website and AI-based Indonesian teaching materials integrated with arts and cultural values - Zuhad Zuhad; Carrine Irawan Kumalasari; Cahyo Hasanudin; Aji Krisna Bayu; Liga Alhaqi Audi Putra Nusantara (BAHASTRA, 2026)
Developing Indonesian language teaching materials that address 21st century demands has become a necessity. This study aims to design AI-integrated and web-based Indonesian teaching materials that are integrated with art and cultural values. It focuses on student interaction with AI as cultural interpreter and the embedding of cultural values within learning activities. This study implements ADDIE design. The primary novelty of this research lies in the formulation of a tripartite integration framework that simultaneously unifies three core components within a single learning product. The research subjects were 200 junior high school students. Data was collected through student needs assessment questionnaires, expert validation questionnaires, and learning achievement tests. The needs analysis revealed a high demand for interactive digital teaching materials among students, with the aspects of digital teaching materials (4,15) and learning technology (4,10) ranking as the highest priorities. Expert validation results indicated that material and media feasibility achieved scores of 90,8% and 88,4%, both categorized as “highly feasible.” The N-Gain test results demonstrated that the experimental class attained an average score of 0,60 (moderate category), with 60% of students falling into the high category, whereas the control class only achieved 0,28 (low category). Pedagogical implication of these findings is the need of learning model which integrates technology and culture to create meaningful, contextual and responsive learning experience. Therefore, AI-integrated and web-based Indonesian teaching materials integrated with art and cultural values are declared highly feasible and effective for use at junior high school level. This study offers three significant contributions: (1) a theoretical contribution in form of the tripartite integration framework, (2) a practical contribution through a ready-to-implement teaching material product, and (3) a policy contribution as a reference for developing an Indonesian language curriculum that is adaptive to the digital era while simultaneously preserving local culture.